The First Successful Implementation of Family-Centered Health Care in Pediatric Intensive Care Unit in Republic of Kazakhstan (Report) - Askhat I. Saparov; Vitaly G. Sazonov; Zaure S. Tobylbaeva; Gauhar B. Karina; Mikhail N. Kurochkin; Didar K. Beremzhanova; Aizhan Z. Mұstafa (Общая реаниматология)
The Leiden Charter for Children in Hospital states that children in hospital shall have the right to have their parents or parent substitute with them at all times (European Association for Children in Hospital (EACH) 1988).In this report, the technology chain for the implementation of the patient's parent/guardian resident stay model (RSM) in pediatric anesthesiology, resuscitation and intensive care unit (PARICU) was presented.The aim of the report was to share the experience in improving patient safety and transparency of intensive care and introducing the active patient care through a «double control». The implementation of RSM has contributed to building a trustful interaction between parents/guardians and medical staff, developing skills for the proper care of children.The 24-hour family-centered care in PARICU was favorably evaluated by parents/guardians and, according to preliminary data, helped to stabilize the condition and improve the well-being of patients.